Lifestyle and incident dementia: A COSMIC individual participant data meta-analysis - Van Asbroeck S; Köhler S; van Boxtel MPJ; Lipnicki DM; Crawford JD; Castro-Costa E; Lima-Costa MF; Blay SL; Shifu X; Wang T; Yue L; Lipton RB; et al. (Wiley Periodicals LLC on behalf of Alzheimer's Association, 2024)
INTRODUCTION: The LIfestyle for BRAin Health (LIBRA) index yields a dementia risk score based on modifiable lifestyle factors and is validated in Western samples. We investigated whether the association between LIBRA scores and incident dementia is moderated by geographical location or sociodemographic characteristics. METHODS: We combined data from 21 prospective cohorts across six continents (N = 31,680) and conducted cohort-specific Cox proportional hazard regression analyses in a two-step individual participant data meta-analysis. RESULTS: A one-standard-deviation increase in LIBRA score was associated with a 21% higher risk for dementia. The association was stronger for Asian cohorts compared to European cohorts, and for individuals aged ≤75 years (vs older), though only within the first 5 years of follow-up. No interactions with sex, education, or socioeconomic position were observed. DISCUSSION: Modifiable risk and protective factors appear relevant for dementia risk reduction across diverse geographical and sociodemographic groups. HIGHLIGHTS: - A two-step individual participant data meta-analysis was conducted. - This was done at a global scale using data from 21 ethno-regionally diverse cohorts. - The association between a modifiable dementia risk score and dementia was examined. - The association was modified by geographical region and age at baseline. - Yet, modifiable dementia risk and protective factors appear relevant in all investigated groups and regions.
Keywords: age; dementia; dementia risk reduction; education; effect modification; ethnicity; individual participant data meta‐analysis; interaction; lifestyle; primary prevention; region; risk factor; risk personalization; sex; socioeconomic; Humans; Dementia; Life Style; Male; Female; Risk Factors; Aged; Prospective Studies; Incidence